Combining ability analysis in bread wheat (Triticum aestivum) over environments - Kumar, Pawan; Singh, Hoshiyar; Lal, Chhagan; Sharma, Sheetal Raj (The Indian Journal of Agricultural Sciences, 2020)
The purpose of the study was to analyze combining ability in bread wheat (Triticum aestivum L.) for yield and its contributing traits over environments. Ten genetically diverse parents were crossed in half diallel fashion excluding reciprocals and the trial was arranged in a Randomized Block Design with three replications during rabi 2016-17 at research farm, Rajasthan Agricultural Research Institute (RARI), Durgapura, Jaipur. The outcomes from current study demonstrated significance of GCA and SCA for all the characters indicated the importance of both type of gene action. The GCA/SCA variance ratio indicated the preponderance of non-additive gene action except Number of tillers per plant for F1 generation in very late sown environment which showed preponderance of additive gene action. An overall evaluation of GCA effects and per se performance over the environments showed that the parent PBW 343, Raj 4079 and Raj 4083 in all three environments; PBW 590 in normal sowing and late sowing environment emerged as good general combiners while the cross Raj 4079 Ã— Raj 4083 in all the three environments emerged as good specific cross combinations for grain yield.